J. M. Blázquez Martínez et alli. Historia de España. España Romana (218 a.C.-414 d.C.). Madrid, 1982, 1: 646 pp.+1343 figs.; II: 764 pp.+4l4 figs. - Montero Herrero, Santiago (Gerión. Revista de Historia Antigua, 1984)
Sin resumen